2018
DOI: 10.1007/s10900-018-0589-7
|View full text |Cite
|
Sign up to set email alerts
|

HPV Vaccine-Related Research, Promotion and Coordination in the State of Georgia: A Systematic Review

Abstract: Context: Human papillomavirus (HPV) vaccine was first recommended for female adolescents in the United States in 2006, and for male adolescents in 2011. In 2016, national HPV vaccine coverage was 43.4%, and slightly higher in Georgia (45.6%). Little is known about sub-state-level variation in HPV vaccination or Georgia specific research conducted to improve HPV vaccine uptake. We aimed to describe current uptake of HPV vaccination and synthesize Georgia-specific research of HPV vaccine uptake. Methods:We revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…From the SEM, we included questions beyond the P3 Model including community and policy-level factors that facilitate or hinder vaccine uptake. The frameworks applied to this study address limitations in existing rural health literature on HPV vaccination by considering healthcare system components beyond patient-level factors influencing parents’ and young adults’ vaccination decisions [ 25 , 27 ].
Fig.
…”
Section: Methodsmentioning
confidence: 99%
“…From the SEM, we included questions beyond the P3 Model including community and policy-level factors that facilitate or hinder vaccine uptake. The frameworks applied to this study address limitations in existing rural health literature on HPV vaccination by considering healthcare system components beyond patient-level factors influencing parents’ and young adults’ vaccination decisions [ 25 , 27 ].
Fig.
…”
Section: Methodsmentioning
confidence: 99%
“…23 This framework addresses limitations in existing rural health literature on HPV vaccine by considering healthcare system components beyond patient-level factors in uencing parents' and young adults' vaccination decisions. 15,23 From the socio-ecological model, we included questions beyond the P3 Model including community and policy level factors.…”
Section: Interview Guide Developmentmentioning
confidence: 99%
“…14 Limited research has focused on rural underserved communities related to the HPV vaccine. 15 Research has examined facilitators and barriers at the patient-(adolescent & parent), provider-, and practice-levels. The facilitators at both the patient-and provider-levels are patient's trust in the provider, knowledge of the vaccine, and self-e cacy in one's own ability to discuss the vaccine.…”
mentioning
confidence: 99%
“…Other immunization registry studies with more representative samples reported lower local HPV vaccination coverages within several states. [16][17][18][19][20][21][22][23] There are no nationwide populationbased reports to provide national HPV vaccination estimates and comparable state-level estimates. Moreover, the cross-sectional nature of surveys does not allow for projection of vaccination coverage over time to assess how far the United States is from attaining the Healthy People 2020 goal.…”
mentioning
confidence: 99%